Inter-trophic food provisioning between sea and land: The jaguar (panthera onca) as provider of sea turtle carcasses to terrestrial scavengers - Carrillo, Eduardo (2017)
A more complete perspective of carrion use by terrestrial vertebrates and about the role of predators in net carrion supply will improve our understanding of critical ecological processes, particularly those associated with energy flow and trophic interactions. Therefore, the aims of this work were: 1) to record the scavenger species which are benefited indirectly by the predator-prey relationship between jaguars and sea turtles, and 2) to evaluate the influence of activity of vultures on the feeding behavior of the jaguar on sea turtles. During the study period a total of 24 predation events on sea turtles by jaguars were recorded at Nancite beach, Costa Rica. We recorded a total of 11 vertebrate species scavenging on sea turtle carcasses. In this paper, we found that the number of days that the jaguars fed on a sea turtle carcass was correlated with the number of days that the vultures took to find the sea turtle carcass. Our work concluded that the ecological value of jaguars as a top predator, flag, umbrella and keystone species includes their role as a provider of carcasses to scavengers.